Statistical Thermodynamics and Surface Phase Transitions of Interacting Particles Adsorbed on One-Dimensional Channels Arranged in a Triangular Cross-Sectional Structure - Pasinetti, Pedro Marcelo (2009)
Monte Carlo simulations and finite-size scaling analysis have been carried out to study the critical behavior in a submonolayer lattice-gas, which mimics a nanoporous environment. In this model, one-dimensional chains of atoms were arranged in a triangular cross-sectional structure. Two kinds of lateral interaction energies have been considered: (1) wL, interaction energy between nearest-neighbor particles adsorbed along a single channel and (2) wT, interaction energy between particles adsorbed across nearest-neighbor channels. We focus on the case of repulsive transverse interactions (wT > 0), where a rich variety of structural orderings are observed in the adlayer, depending on the value of the parameters kBT/wT (kB being the Boltzmann constant) and wL /wT. For wL /wT = 0, successive planes are uncorrelated, the system is equivalent to the triangular lattice, and the well-known (√3x√3) [ (√3x√3)* ] ordered phase is found at low temperatures and a coverage, θ, of 1/3 [2/3]. In the more general case (wL /wT ≠ 0), the competition between interactions along a single channel and the transverse coupling between sites in neighboring channels leads to a three-dimensional adsorbed layer. Consequently, the (√3x√3) and (√3x√3)* structures "propagate" along the channels and new ordered phases appear in the adlayer. The influence of each ordered phase on adsorption isotherms, differential heat of adsorption and configurational entropy of the adlayer has been analyzed and discussed in the context of the latticegas theory. Finally, the Monte Carlo technique was combined with the recently reported free energy minimization criterion approach (FEMCA) [F. Romá et al.: Phys. Rev. B Vol. 68 (2003), art. no. 205407] to predict the critical temperatures of the surface-phase transformations occurring in the adsorbate. The excellent qualitative agreement between simulated data and FEMCA results allows us to interpret the physical meaning of the mechanisms underlying the observed transitions.